Metabolomics approach to differentiation of citrus rootstock varieties susceptible or tolerant to Phytophthora nicotianae - Labuschagne, Nico (University of Pretoria, 2018)
The focus of this thesis is on the application of plant metabolomics methodologies to study citrus rootstock tolerance towards the root rot pathogen Phytophthora nicotianae. Initially, the tolerance of 16 citrus rootstocks towards the pathogen was assessed in greenhouse experiments. Rootstocks were categorised as tolerant, moderately tolerant and susceptible to the pathogen, during screening of pathogen inoculated versus healthy plants. The rootstocks Australian trifoliate, Benton citrange, Flying Dragon, Swingle citrumelo, Terra Bella citrumelo and Yuma citrange showed tolerance to P. nicotianae infection. Root materials from selected greenhouse experiments were subsequently used for the metabolomics studies where organic plant-root extracts were separated by means of UPLC/MS. In the first instance, MarkerLynx XS software was used to interrogate the citrus metabolome applying a metabolite fingerprinting analytical strategy. The markers associated with tolerant rootstocks included 259.0963, 313.1433, 327.1592 (m/z) putatively identified as Wyerone, 4‟-prenyloxyresveratrol and Pulverochromenol respectively. This allowed us to find evidence from literature linking the markers with plant self defense in other crops, thus supporting the conception that they are related to tolerance in citrus rootstocks. The potential for acquiring resistance related metabolite markers was demonstrated over successive seasons. In the second instance a predictive model for rapid selection of tolerant rootstocks was developed. The predictive model formulation is a de novo and interesting outcome in this study especially for a non-model plant species such as citrus. To our knowledge this is the first report on the use of plant metabolomics to interrogate the citrus rootstock metabolome in association with P. nicotianae tolerance and for tolerance trait discovery for this plant-pathogen interaction. It is envisaged that these findings may enhance marker assisted selection for citrus rootstocks for local and international breeding programs. Proposed future work includes full annotation of the markers and working towards determining the function of the markers through biochemical pathway discovery.